Voice and Speech Quality Perception Assessment and Evaluation - Jekosch, Ute (Signals and Communication Technology, 2005)
Foundations of Voice and Speech Quality Perception starts out with the fundamental question of: "How do listeners perceive voice and speech quality and how can these processes be modeled?" Any quantitative answers require measurements. This is natural for physical quantities but harder to imagine for perceptual measurands. This book approaches the problem by actually identifying major perceptual dimensions of voice and speech quality perception, defining units wherever possible and offering paradigms to position these dimensions into a structural skeleton of perceptual speech and voice quality. The emphasis is placed on voice and speech quality assessment of systems in artificial scenarios. Many scientific fields are involved. This book bridges the gap between two quite diverse fields, engineering and humanities, and establishes the new research area of Voice and Speech Quality Perception.